Galactin-3 regulation of CDC42 promotes neuronal autophagy following spinal cord injury - Yan, Lei; Zhou, Xun; Li, Qianqiu; Hong, Hongxiang; Wu, Chunshuai; Gao, Yong-Jing; Cui, Zhiming; Xu, Guanhua (Frontiers in Cellular Neuroscience, 2025)
BackgroundSpinal cord injury (SCI) is a debilitating condition within the nervous system with a high disability rate and substantial economic burden. The functional recovery following SCI is enhanced by moderate levels of autophagy but hindered when autophagy becomes excessive. Galectin-3 (GAL3) has been recognized as an autophagy regulator; however, its role in SCI and its associated mechanism are largely unknown.MethodsThe Walsh clamping method was employed to establish a rat SCI model, while a high-concentration glutamate incubation method was used to create an in vitro model of spinal cord neuronal injury. Subsequent to establishing the injury models, the expression levels of GAL3 were detected using QPCR and Western Blot. Immunohistochemical staining was performed to determine the localization of GAL3 expression. SiR-GAL3 or GAL3 inhibitors were utilized to knock down or inhibit GAL3 expression, and behavioral analysis was conducted to assess the recovery of motor function in rats following SCI. Bioinformatics analysis was carried out to explore the mechanism of action of GAL3 post-SCI. Western Blot was used to examine the relationship between the expression levels of GAL3 and autophagy-related proteins following SCI. Sequencing analysis was performed to identify the differential gene expression in spinal cord neurons with knocked-down GAL3 compared to the control group after neural injury, aiming to investigate the mechanism of action between GAL3 and its downstream target gene Cell-division-cycle-42 (CDC42). Co-IP was employed to detect the interaction between GAL3 and CDC42 proteins. Western Blot was used to analyze the relationship between CDC42 and autophagy-related protein expression levels following in vitro stimulation of neurons with GAL3. Molecular biology experiments were conducted to assess the expression levels and localization of CDC42 post-SCI. Behavioral analysis was performed to evaluate the recovery of motor function in rats with inhibited CDC42 expression after SCI. ELISA was used to measure the expression levels of GAL3 and CDC42 in both rat and human samples post-SCI.ResultsWe found that GAL3 was increased in spinal neurons and serum in SCI rats, and knockdown or inhibition of GAL3 promoted motor function recovery. The bioinformatics analysis showed that GAL3 is closely related to programmed cell death after SCI. Indeed, the knockdown of GAL3 resulted in a decrease in autophagy markers ATG7 and LC3 II/I ratio, along with an increase in P62 expression. Furthermore, GAL3 and CDC42 exhibited close associations with neuronal autophagy. Injection of siR-CDC42 and CDC42 inhibitor ML141 effectively reduced GAL3-mediated enhancement of neuronal autophagy. Additionally, CDC42 was increased in spinal neurons post-SCI, and administration of ML141 decreased the expression of autophagy markers and improved motor function recovery. Importantly, elevated levels of GAL3 and CDC42 were observed in the serum of SCI patients.